Cost Analysis of Haemodialysis Patients in Government Tertiary Care Centre – A Pharmacoeconomic Study - Manjula MJ; Deepak P; Suresh R M; Raghu N (Universitas Padjadjaran, Indonesia, 2021)
The progression of chronic kidney disease (CKD) to End-Stage Renal Disease (ESRD) in India is rapidly increasing. Over 25 million of people suffering from ESRD, especially in rural areas. Many of these patients are not undergoing dialysis due to the factors such as lack of awareness, fewer treatment options, unaffordability prices due to low income, and minor reimbursement for chronic illness. The cost of hemodialysis in private hospitals is around 12.000 INR (Indian Rupee) per person monthly and 140.000 INR per year, which seem too expensive for middle and lower-middle-class of patients. Hence our study was aimed to analyze the healthcare cost of hemodialysis in government tertiary health care centers by analyzing the direct and indirect cost from the patient perspective. Sixty patients who underwent dialysis in Hassan Institute of Medical Sciences Teaching Hospital were included in this study. The demographic details, past and present medical history, cost per session of dialysis, laboratory examination, money spent on travel, and the working days lost were calculated. Out of 60 patient (male: 47; female: 17), 53 patients aged 18-65 years old. They belonged to lower-middle (38.33%), middle (23.33%), lower (21.66%), and upper-middle-class (8%). The average direct medical cost of each patient in one session of dialysis was 481.5 INR and indirect medical costs were 557.33 INR. Based on our observation, we conclude that the patients are having satisfactory outcomes, comparatively at low cost in our government dialysis unit. Government should encourage and also cover the mobile dialysis centers under government health schemes, by which the indirect medical cost can be reduced.